Evaluation of the Role of Community Capacity Building on Sustainability of the Millenium Villages Food Security Project in Barsauri-Gem,Kenya - Okoth, Richard Owino (JOOUST, 2015)
Community capacity building is essential for sustainability of donor funded projects especially food security projects such as Millennium Villages Project in Barsauri, Gem. MVP funded by United Nations through the Millennium Villages was started in 2004 and funded for four years after which the project was to be self-sustaining through a well built community capacity. Sustainability is still a major challenge in many developing countries and therefore for it to be achieved, the community a project targets should be well equipped to carry on the work even after the funding period ends. The purpose of the study was to establish the extent to which community capacity building influenced sustainability of Millennium Village Food security Project in Bar sauri, Gem sub-county. Specifically, the study strived to establish the extent to which financial capacities, human capacities and community organization capacity building could influence the sustainability of MVP. I used survey design to cover a population of 33 respondents in Barsauri location, Gem sub-county. The respondents comprised of 11 village elders, 3 assistant chiefs, 8 women representatives,6 youth leaders and 5 MVP field officers. Using a self administered questionnaire and in-depth interviews, emerging data was analyzed using simple descriptive statistics like mean and standard deviations. The findings indicate that financial capacity building had a high influence on project sustainability. Also training had a high influence on project sustainability. Finally, community organizing approaches had a very high influence on sustainability. I concluded that the financial, technical and managerial self reliance aspects of project sustainability are significantly dependant on the kind of efforts by the management of the MVP. By building capacity through financial support, human resource training and community organizing approaches, there is a high possibility of ensuring sustainability. I therefore draw a number of managerial and theoretical implications whose scope appeals to a wide range of audiences both at the village and national levels.
Keywords: Capacity Building; Project; Sustainability; Millennium Villages Project